2000
DOI: 10.1007/s100670070049
|View full text |Cite
|
Sign up to set email alerts
|

Serum Creatine Kinase in Patients with Rheumatic Diseases

Abstract: Serum creatine kinase (CK) activity is reduced in some conditions, including rheumatic diseases, but the aetiology and significance remain to be clarified. The aim of this study was to investigate relationships between serum CK activity and other muscle enzymes, muscle mass, renal function, steroid use and disease activity in patients with rheumatic diseases. Serum CK activity was measured in sera from 498 patients with rheumatic diseases: rheumatoid arthritis (RA, n = 145), systemic lupus erythematosus (SLE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…Additionally they showed a high predominance of the S3 allele and concluded causality. Lee et al [22] found elevated Lp(a) levels in RA patients compared to controls as well. Although Lp(a) tended to be higher in RA, they could not find a distinct acute phase pattern of Lp(a).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally they showed a high predominance of the S3 allele and concluded causality. Lee et al [22] found elevated Lp(a) levels in RA patients compared to controls as well. Although Lp(a) tended to be higher in RA, they could not find a distinct acute phase pattern of Lp(a).…”
Section: Resultsmentioning
confidence: 99%
“…Inflammatory conditions including rheumatoid arthritis and systemic lupus are associated with reduced CK levels. 15 Statins reduce systemic inflammation 1 and could increase average CK by decreasing inflammation. We did not measure inflammatory markers in STOMP so cannot evaluate this possible relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Serum CK has been shown to be lower in patients with RA versus healthy volunteers and to correlate with the level of inflammation [35]. Generally, mean CK tended to plateau after six months of tofacitinib treatment, stayed within the normal reference range and was not associated with clinical myopathy or changes in markers of muscle catabolism (lactate dehydrogenase and myoglobin).…”
Section: Discussionmentioning
confidence: 99%